Free exercise: religion, the First Amendment, and the making of America - Beneke, Chris (Oxford University Press, 2024)
"Free Exercise is a contribution to both US constitutional history and the history of religious toleration in the United States. It traces the routes by which Americans arrived at the First Amendment's religious clauses, the cultural currents that shaped their meaning, and the consequences that flowed from them. The book also demonstrates how white women, African Americans, Jews, Roman Catholics, and nonbelievers expanded the application of religious liberty-and illuminated its boundaries. Each chapter demonstrates how protections for religious freedom were forged from both vague memories and intimate experiences, an emergent respect for individual autonomy and a refusal to materially alter the condition of women and the enslaved"--Publisher